Materiais didáticos em Limnologia como recurso pedagógico para educadores - Moura, Vitória Fabri de (Universidade Federal de São Carlos, 2022)
Most of today's societies, inserted in the globalized world, have adopted abusive ways of life regarding water consumption. Water is of fundamental importance in the maintenance of the life of living beings, and Environmental Education (EE) is one of the main and most important means to ensure attitudes that impact on the conservation of springs and water bodies, being able to form generations that intervene and effectively solve environmental challenges and problems. EE directly influences the formation of generations that will use natural resources, shaping habits, in addition to shaping the way in which the improvement of sustainable development occurs and will occur. The term EE is increasingly present in Brazilian society, especially regarding water conservation, an abundant resource in the country. The perception of the environment and resources is an individual mental process, based on the individual relationship with the environment. It is essential that the child and adolescent have full knowledge so that it is possible to form and cognize a conscious citizen, who works in sustainable development. This study aimed to analyze, propose, and develop teaching materials that include EE for water conservation in line with SDG 6, with participatory methodologies in EE about Limnology. To formulate the materials, a research and study of selected materials were carried out, consisting of review articles, original articles, full articles in the annals of scientific events, monographs, dissertations and theses published between 2011 and 2021, with the descriptors: basic sanitation, waterborne diseases, water pollution and teaching material. In the last 10 years, the main means of teaching children and young people in EE have been introduced in other disciplines. They are interactive and practical, adapted for the age groups, with the objective of assertiveness, interaction, and development of a critical sense in practice, and that seek participatory and fun ways to retain knowledge. This analysis indicated the broad possibility of propositions and applications of pedagogical strategies following the United Nations (UN) Sustainable Development Goals focused on SDG 6 (Drinking Water and Sanitation).
Teaching materials in Limnology as a pedagogical resource for educators
Keywords: Educação Ambiental; Sustentabilidade; Limnologia; Environmental education; Sustainability; Limnology; CIENCIAS BIOLOGICAS::ECOLOGIA